1994
DOI: 10.1346/ccmn.1994.0420501
|View full text |Cite
|
Sign up to set email alerts
|

Prograde Transitions of Corrensite and Chlorite in Low-Grade Pelitic Rocks from the Gaspé Peninsula, Quebec

Abstract: Abstract-A prograde sequence ofcorrensite and chlorite in pelitic rocks of the diagenetic zone, anchizone, and epizone (illite crystallinity indices = 0.17-0.58~ of the Gasp6 Peninsula, Quebec, was studied by analytical and transmission electron microscopy (AEM and TEM). The data collectively suggest that diagenesis/metamorphism of chlorite and corrensite follows a sequence of phase transitions, compositional homogenization, and recrystallization, approaching a state of equilibrium for which chlorite is the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 67 publications
2
34
0
Order By: Relevance
“…The analyses of corrensite are similar to those of Inoue (1985), Shau et al (1990), Shau and Peacor (1992), Jiang and Peacor (1994b), and Schiffman and Staudigel (1995), with higher Si and Na + K + Ca contents and slightly lower values of Fe/(Fe + Mg) than chlorites. Higher substitutions of octahedral Fe 2+ for Mg 2+ in the chlorites may compensate for the distortions introduced by the substitution of the larger A13+ cation for Si 4+ in the tetrahedral sheet (Shau et al, 1990).…”
Section: Compositional Variations Of Chlorite and Corrensitesupporting
confidence: 74%
See 1 more Smart Citation
“…The analyses of corrensite are similar to those of Inoue (1985), Shau et al (1990), Shau and Peacor (1992), Jiang and Peacor (1994b), and Schiffman and Staudigel (1995), with higher Si and Na + K + Ca contents and slightly lower values of Fe/(Fe + Mg) than chlorites. Higher substitutions of octahedral Fe 2+ for Mg 2+ in the chlorites may compensate for the distortions introduced by the substitution of the larger A13+ cation for Si 4+ in the tetrahedral sheet (Shau et al, 1990).…”
Section: Compositional Variations Of Chlorite and Corrensitesupporting
confidence: 74%
“…Hillier (1993) suggested that coexisting Mg and Fe-rich chlorites within a diagenetic mudrock are indicative of disequilibrium at the microscopic scale. In contrast, Jiang and Peacor (1994b) and Jiang et al (1994) described heterogeneous chlorite compositions in diagenetic and anchizonal samples, which become progressively more homogeneous in the epizone. In our study, metamorphic conditions estimated from IC and ChC data are between anchizone and epizone, which is consistent with the observed homogeneity in chlorite compositions within a given sample.…”
Section: Compositional Variations Of Chlorite and Corrensitementioning
confidence: 84%
“…The first includes five pelitic rocks (A419, A416, R299, 89-12, and R245) as part ofa prograde sequence ranging from the diagenetic zone to the epizone (illite crystallinity indices = 0.19-0.58 ~ A20 for ethylene glycol solvated < 2 #m fractions) in the Gasp6 Peninsula, Quebec (Jiang and Peacor 1994). The diagenetic rocks (samples A419 and A416) contain discrete chlorite, and corrensite and illite that locally occur as intimate intergrowths with chlorite (Figure 1 a).…”
Section: Samples and Methodsmentioning
confidence: 99%
“…Interstratified Chl/Vrm present in some samples could correspond to a metaestable phase from which chlorite formed, being part of the prograde reaction series corrensite→corrensite-chlorite→chlorite. The presence of intermediate phases belonging to this series, in which the vermiculite would be generated by detrital biotite alteration (Bozkaya and Yalçin, 2004), is consistent with late diagenetic conditions (Jiang and Peacor, 1994;Merriman and Peacor, 1999). However, some of the samples containing interstratified Chl/Vrm show KI (CIS) values corresponding to high-anchizone conditions (e.g., Achavil Formation), under which Chl/Vrm is generally not stable, and it seems more likely they are the product of retrograde reactions.…”
Section: Significance Of Chl/vrm Through the Cambro-ordovician Succesmentioning
confidence: 52%